Sistem Klasifikasi Ikan Tongkol yang mengandung Formalin dengan Sensor HCHO dan Sensor pH menggunakan Metode K-Nearest Neighbor berbasis Arduino - Dedi Siswanto; Dahnial Syauqy; Agung Setia Budi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Tuna has a high protein content that can meet the nutritional needs of the human body. One of the sea fish that contains omega 3, vitamins, protein, and minerals is tuna. Tuna meat is a type of meat that is easily damaged (rot). Usually to avoid damage of fish, fishermen and sellers usually preserve fish using ice cubes. However, preserving fish using ice cubes requires large amounts of ice cubes, thereby reducing the amount of profit gained and also impractical. To replace ice cubes, usually cheat seller use dangerous chemicals such as formalin. To overcome the cheating, it is needed a classification system for tuna that contains formalin. This system uses several components, such as: arduino mega 2560 microcontroller to process data and calculate k-nearest neighbor, HCHO sensor which is used for detecting HCHO gas released by formalin, and pH sensor used to measure of the pH value in tuna. The system to distinguishing tuna that contains formalin with tuna that does not contain formalin using the k-nearest neighbor method gets 90% accuracy. Test the K value by using odd numbers 3, 5, 7, 9. After that, the results of changes in value K are compared to see which K values are more accurate on the k-nearest neighbor method applied to the system.